Promoter context determines the role of proteasome in ligand-dependent occupancy of retinoic acid responsive elements - Higazi, Aliaa (Landes Bioscience, 2011)
Retinoid acid receptors are DNA-binding proteins mediating the biological effects of ligands through transcriptional activation. It is known that the activity of the 26S proteasome is important for nuclear receptor-activated gene transcription. However, the molecular mechanism by which the 26S proteasome participates in this process is not well understood. Here we report that the proteasome activity is essential for ligand-dependent interaction of RAR with its co-regulators such as SRC, p300 and RXR. We also determined that the proteasome activity is required for the association of liganded RAR to the genomic DNA and, consequently, for the recruitment of the coactivator complex to the retinoic acid responsive elements. Moreover, the requirement of proteasome activity for the activator activity of RAR is determined by the promoter context. Our study suggests that the 26S proteasome regulates directly the activity of RAR as an activator.